Synthetic Studies on Acochlearine: Construction of the A/B/C/E/F Ring System - Fujioka, Kosuke; Miyamoto, Naoya; Toya, Hiroki; Okano, Kentaro; Tokuyama, Hidetoshi (Synlett, 2016)
Synthetic studies on acochlearine are described. The pentacyclic A/B/C/E/F ring system of acochlearine was constructed from a bicyclic enone via chemoselective reductive amination, one-pot bromination–intramolecular Mannich reaction cascade, and 6π-electrocyclization.
Keywords: alkaloids; halogenation; lactams; domino reaction; Mannich reaction; C–H functionalization